2015
DOI: 10.1089/ten.tea.2014.0254
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based Reconstruction of the Inferior Vena Cava in Rat: Stem Cells or RGD Peptide?

Abstract: As part of a program targeted at developing a resorbable valved tube for replacement of the right ventricular outflow tract, we compared three biopolymers (polyurethane [PU], polyhydroxyalkanoate (the poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-4-hydroxyvalerate) [PHBVV]), and polydioxanone [PDO]) and two biofunctionalization techniques (using adipose-derived stem cells [ADSCs] or the arginine-glycine-aspartate [RGD] peptide) in a rat model of partial inferior vena cava (IVC) replacement. Fifty-three Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Studies of in vitro MSC differentiation on electrospun PDO are limited. Electrospun PDO scaffolds have shown to facilitate growth of human dental pulp stem cells and differentiation of adipose‐derived stem cells down adipogenic and chondrogenic cell lines in vitro . In vivo studies have shown that electrospun PDO scaffolds facilitate the differentiation of MSCs into vascular tissue …”
Section: Introductionmentioning
confidence: 99%
“…Studies of in vitro MSC differentiation on electrospun PDO are limited. Electrospun PDO scaffolds have shown to facilitate growth of human dental pulp stem cells and differentiation of adipose‐derived stem cells down adipogenic and chondrogenic cell lines in vitro . In vivo studies have shown that electrospun PDO scaffolds facilitate the differentiation of MSCs into vascular tissue …”
Section: Introductionmentioning
confidence: 99%
“…Figure depicts electron microscopy pictures of the electrospun non‐wovens mats. In all cases, the co‐electrospinning proceeded well, and the fiber orientation, fiber diameter and porosity (see Table ) were comparable for all investigated samples and are very similar to pure electrospun PPDO …”
Section: Resultsmentioning
confidence: 62%
“…PPDO patches co‐electrospun with unmodified (free) RGD (Ac‐Gly‐Arg‐Cys‐Gly‐Arg‐Gly‐Asp‐Ser‐Pro‐Gly‐NH 2 ) were prepared as previously reported …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDO electrospun tissue-engineered valved transannular patch appears to be a promising device in restoring a living RVOT and could ultimately lead to applications in the treatment of congenital RVOT diseases. The same group further compared electrospun scaffolds of PU, poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-4-hydroxyvalerate (PHBVV) and PDO, using two biofunctionalization techniques: adipose-derived stem cells or arginine-glycine-aspartate (RGD) peptide in a rat model of partial inferior vena cava replacement [117]. In vitro studies using adipose-derived stem cells and in vivo results revealed the superior properties of PDO, while the two functionalization methods yielded similar outcomes.…”
Section: Scaffolds Based On Other Polymeric Materialsmentioning
confidence: 99%